The Efforts of Islamic Religious Education Teachers in Developing Students' Religious Culture at Elementary Schools in Sidoarjo Regency: Upaya Guru Pendidikan Agama Islam dalam Mengembangkan Budaya Religius Siswa di Sekolah Dasar Kabupaten Sidoarjo - Alkorni, Wais; Fauji, Imam (Universitas Muhammadiyah Sidoarjo, 2023)
In this regard, Celep State Elementary School, Sidoarjo Regency, applies religious activities that are implemented in schools. This study aims: 1) To find out the efforts of Islamic Religious Education Teachers in developing the religious culture of students at SD Negeri Celep, Sidoarjo Regency, 2) To find out the implementation of religious culture in shaping the morals of students in Celep State Elementary Schools, Sidoarjo Regency. 3) To find out what factors hinder Islamic Religious Education Teachers in developing a religious culture at SD Negeri Celep, Sidoarjo Regency. To achieve this goal, this study uses a qualitative method with a descriptive approach. Data collection techniques used (1) interviews, (2) observations, (3) drawing conclusions. To check the validity of the data, the author uses triangulation and peer checking. This study reveals that in the process of creating a religious culture at the Celep State Elementary School, Sidoarjo Regency, it is implemented in several ways, including: 1) The efforts of Islamic Religious Education Teachers in Developing the Religious Culture of Students at State Elementary Schools Celep Sidoarjo Regency. includes 5S Dzuhur Prayer, Taur saqu, Islamic holiday celebrations. 2) the implementation of religious culture at SDN Celep has given a very positive response, it can be seen from how students when dressing speak, behave, and respect time, are independent, disciplined, honest, tolerant and socially concerned. 3) inhibiting factors, namely: Insufficient places of worship, lack of human resources.